A review of foster home policies and regulations in the United States designed to support foster homes families. Issue 2 (14th March 2020) - Jedwab, Merav; Chatterjee, Anusha; Shaw, Terry V.
ABSTRACT: Foster parents are required to learn and to navigate a range of policies and regulations in order to make decisions that are in the best interest of the foster child. This paper reviews four policies and regulations (foster parent handbooks, pre-service and in-service training, respite care, and information on points of contact) intended to support family foster homes and examines whether these policies and regulations are available and accessible to the foster parents. Data were collected using a mixed methods research design, including an online search and a survey for child welfare administrators. Findings and implications for policy and practice are discussed.